NEGOTIATING LANGUAGE IDEOLOGIES AND ETHICAL BOUNDARIES: LECTURERS’ NARRATIVES ON AI USE IN ENGLISH LANGUAGE TEACHING - Pujiani, Tri; Istifani, Lilia; Khoiron, Muhammad Pandu (IJIET (International Journal of Indonesian Education and Teaching), 2026)
The rapid evolution of AI in education has triggered contentious debates over its ethical use and effects on language learning. This study investigated how English teachers negotiate and appeal to language ideologies and ethical boundaries as they respond to AI tools in English Language Teaching (ELT). Grounded on language ideology and pedagogical technology theories, the research employed narrative inquiry design in examining the Indonesian university lecturers' experiences of language, ethics, and AI-driven classroom practice. Preliminary screening questionnaires and narrative in-depth interviews were used in collecting the data. The findings demonstrate that while AI tools have become valued for efficiency in supplying grammatical correction, lecturers are worried that the reliance on AI might hinder critical thought and emergence of agency. Lecturers also note the inadequacy of AI at engaging the local diversity of languages and dialects, and AI often tends to construct a standardized version of English. The study indicates that AI can be a useful tool in ELT by offering feedback and improving language accuracy, but caution is necessary to maintain academic integrity and ensure meaningful learning. This research contributes to the conversation on AI in education, offering actionable insights on ethical and productive AI use in language teaching.